Identification of the critical success factors for public-funded R&D projects in South Africa - Mkhize, Bahle (Department of Construction Economics and Management, 2019)
South Africa (SA) is classified as a middle-income emerging market, with the most resource-rich economy in Sub-Saharan Africa (SAccess, 2012). Its Research and Development (R&D) journey is characterised by a history of imbalances and oppression. Since the introduction of SA’s National R&D Strategy, recorded government R&D spending has been on the rise. However, the success rate for public-funded R&D projects has neither been satisfactory nor readily exposed for all to see. Factors considered critical for project success are largely contextual and tend to differ per project and industry. There appears to be no general consensus among scholars and authors on the common factors deemed critical in influencing the success of public-funded R&D projects. In SA, such factors still remain a mystery for further exploration. This research study sought to develop a model that will assist in achieving two key objectives, namely to identify the Critical Success Factors (CSF) of public-funded R&D projects in SA, as well as to exhume possible interrelationships between the identified critical success factors. This paper argues for a systemic and structure-based holistic approach and adopts Warfield’s Interactive Management (IM) in its endeavour to identify those factors that are deemed critical in the successful implementation of public-funded R&D projects in SA. The methodology comprises three key phases: a planning phase; a workshop phase; as well as a follow-up phase. The planning phase is a foundational phase that lays the basis and a plan for the ensuing two phases. The workshop, also known as the conversation phase, could be conceptualised as a process for building patterned interactions among the participants. It is in this phase that a relationship model, in the form of a diagraph, is constructed. The follow-up phase is the last phase and involves the implementation of the results to prove validity of solutions proposed in the workshop phase. However, since this last phase falls outside the scope of this paper, it has been excluded. Through the application of the IM methodology, a total of 35 identified CSFs were reduced to 23 key to formulate the CSF relationship model using the Interpretive Structural Model (ISM). Based on the model results, the study is concluded by identifying “Product market viability” and “Executive management support” as the two primary success factors that are most significant and have the greatest leverage to influence other factors towards the successful completion of public-funded R&D projects in SA.